ANALISIS PENGARUH SIZE, PROFITABILITY, CAPITAL ADEQUACY, DAN NON-PERFORMING LOAN TERHADAP LIKUIDITAS BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Bramantya, Bintang; Arfianto, Erman Denny (Diponegoro Journal of Management, 2015)
Banks play an important role in economic activity of a country. Bank is a financial institution trusted by the community to manage the funds. Banks are required to always be able to maintain the level of liquidity and profitability.This study aims to analyze the effect of size, profitability, capital adequacy, and Non-Performing Loan on bank liquidity. The sample used in this study are commercial banks listed in Indonesia Stock Exchange during the years 2011 through 2014. The sampling technique used in this research is purposive sampling method covering 27 banks as samples. The analysis method used in this study is Normality Test, Autocorrelation Test, Multicolliniarity Test, Heteroscedasticity Test, Coefficient of Determination Test, F Statistic Test, t Statistic Test, and Multiple Linear Regression Analysis.Based on the results of the partial testing carried out, size and profitability have positive effect on liquidity. Meanwhile, capital adequacy and Non-Performing Loan have negative effect on liquidity. Based on the test results of Coefficient of Determination Â Test, the variable size, profitability, capital adequacy and Non-Performing Loan has an effect on the liquidity of 22,50%.